A glass fiber composite flame retardant modified polycarbonate material and preparation process

By adding quaternary ammonium modified glass fibers and hexa(carbazoleanilinyl)cyclotriphosphazene flame retardant to the polycarbonate, the problems of poor flame retardancy and insufficient dispersion of glass fibers are solved, and the efficient flame retardant and mechanical properties of polycarbonate are achieved.

CN118546510BActive Publication Date: 2025-03-21FOSHAN NANHAI POLMA ENG PLASTIC CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410595336.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-13
Publication Date
2025-03-21
Estimated Expiration
2044-05-13

AI Technical Summary

Technical Problem

Polycarbonate has poor flame retardancy and the dispersion of glass fibers in polycarbonate is insufficient, which affects its performance.

Method used

Quaternary ammonium modified glass fiber and hexa(carbazoleanilyl)cyclotriphosphazene flame retardant are added to the polycarbonate, and the flame retardant is modified to the surface of the glass fiber through a blending process to form a flame retardant glass fiber composite material.

Benefits of technology

The ultimate oxygen index of polycarbonate is significantly improved, and the UL94 fire resistance level reaches V-0 level, while improving its tensile strength and flexural modulus.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004839655040000031
    Figure BDA0004839655040000031
  • Figure BDA0004839655040000051
    Figure BDA0004839655040000051
  • Figure BDA0004839655040000061
    Figure BDA0004839655040000061
Patent Text Reader

Abstract

The present invention relates to the technical field of polycarbonate, and discloses a flame-retardant modified polycarbonate material and a preparation process of a glass fiber composite material, including 100 parts by weight of polycarbonate, 0.05-0.3 parts by weight of hexa(sulfonic acid carbazole aniline) cyclotriphosphazene, and 2-20 parts of quaternary ammonium salt modified glass fibers; the present invention modifies the hexa(sulfonic acid carbazole aniline) cyclotriphosphazene flame retardant to the surface of the glass fiber. The two form a flame-retardant glass fiber composite material, which significantly improves the limiting oxygen index of polycarbonate, and the UL94 fire rating reaches V-0 level. The modified glass fiber surface is modified with an organic functional group, which improves the compatibility with polycarbonate, so that the glass fiber can be evenly dispersed in a polycarbonate matrix, and its reinforcing effect is more effectively exerted, thereby improving the tensile strength and flexural modulus of the polycarbonate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polycarbonate, in particular to a glass fiber composite material flame retardant modified polycarbonate material and a preparation process. Background Art

[0002] As a general-purpose plastic with excellent performance, polycarbonate is widely used in glass assembly industry, automobile industry, electronic and electrical industry and other fields. Modifying polycarbonate to improve its mechanical strength, flame retardancy, UV resistance and other properties and expanding the practical application areas of polycarbonate has become a research trend. The main flame retardants for polycarbonate are sulfonate series, nitrogen-phosphorus series, etc.

[0003] As an inorganic non-metallic material with excellent performance, glass fiber has the advantages of high mechanical strength, good insulation, strong heat resistance, good corrosion resistance, etc. It can be used as a reinforcing material for plastics, a heat insulation material, a fireproof shielding material, etc. It is widely used. Improving the compatibility between glass fiber and materials such as polycarbonate can better play the reinforcing effect of glass fiber. Using methods such as plasma surface treatment and silane coupling agent surface modification can effectively improve the surface properties of glass fiber. For example, the document "Study on the Adsorption and Removal of Cr(VI) in Water by Quaternary Ammonium Salt Modified Glass Fiber Filter Paper" discloses that dimethyl octadecyl [3 (-trioxymethylsilyl) propyl] ammonium chloride is grafted with glass fiber filter paper after plasma pretreatment to obtain a glass fiber material loaded with quaternary ammonium salt groups, which has a good application in the treatment of chromium-containing wastewater. Patent CN107690453B discloses a glass fiber reinforced polycarbonate molding compound with improved toughness, using vinyl copolymer, organic surface modified short glass fiber, etc. as raw materials, and improving the toughness, melt flowability, tensile elastic modulus and other properties of polycarbonate. However, the patent does not improve the flame retardant properties of polycarbonate. Summary of the invention

[0004] The invention solves the problem of poor flame retardancy of polycarbonate and improves the dispersibility of glass fiber in polycarbonate.

[0005] Technical solution:

[0006] A preparation process of a flame-retardant modified polycarbonate material of a glass fiber composite material, comprising 100 parts by weight of polycarbonate, 0.05-0.3 parts by weight of hexa(sulfonic acid carbazole aniline)cyclotriphosphazene, and 2-20 parts of quaternary ammonium salt modified glass fiber;

[0007] Furthermore, the preparation process is as follows: adding quaternary ammonium salt modified glass fiber and hexa(sulfonic acid carbazole aniline) cyclotriphosphazene to a twin-screw extruder, setting the screw speed to 20-40 r / min, the blending temperature to 70-90° C., and mixing for 5-10 minutes; then adding polycarbonate, setting the blending temperature to 260-275° C., blending for 5-10 minutes, and extruding to obtain a glass fiber composite material flame retardant modified polycarbonate material.

[0008] Further, the preparation process of hexa(sulfonic acid carbazole aniline)cyclotriphosphazene is:

[0009] (1) Hexachlorocyclotriphosphazene, 9-(4-aminophenyl)carbazole hydrochloride and pyridine are added to a reaction solvent, stirred at 75-90° C. for 48-72 hours in a nitrogen atmosphere, and the solvent is concentrated, washed with acetone, and dried to obtain hexa(carbazoleanilino)cyclotriphosphazene.

[0010] (2) At -20°C to -10°C, add hexa(carbazole aniline)cyclotriphosphazene to dichloromethane, add chlorosulfonic acid dropwise, mix well, react at 15-25°C for 12-24h, concentrate the solvent, wash with acetone, add the product to a potassium hydroxide solution with a pH of 9-11, react for 2-3h, filter, wash with water, and dry to obtain hexa(sulfonic acid carbazole aniline)cyclotriphosphazene. The reaction formula is as follows:

[0011]

[0012] Furthermore, the molar ratio of hexachlorocyclotriphosphazene, 9-(4-aminophenyl)carbazole hydrochloride and pyridine in (1) is 1:(6-6.6):(12-13).

[0013] Furthermore, the solvent in (1) is any one of toluene, xylene and 1,4-dioxane.

[0014] Furthermore, in (2), the molar ratio of hexa(carbazoleanilino)cyclotriphosphazene to chlorosulfonic acid is 1:(18-24).

[0015] Furthermore, the preparation process of the quaternary ammonium salt modified glass fiber is as follows: the short chopped glass fiber is placed in a radio frequency plasma device for plasma pretreatment; the glass fiber is then immersed in an ethanol aqueous solution containing dimethyloctadecyl[3(-trioxymethylsilyl)propyl]ammonium chloride and ethyl orthosilicate; and finally the glass fiber is placed in an oven for chemical grafting reaction to obtain the quaternary ammonium salt modified glass fiber.

[0016] Technical effect: The present invention uses pyridine as a catalyst, and hexachlorocyclotriphosphazene and 9-(4-aminophenyl)carbazole hydrochloride react to obtain hexa(carbazoleaniline)cyclotriphosphazene, which is further sulfonated with chlorosulfonic acid and potassium hydroxide to obtain a novel hexa(sulfonic acid carbazoleaniline)cyclotriphosphazene flame retardant.

[0017] The invention adds quaternary ammonium salt modified glass fiber and hexa(sulfonic acid carbazole aniline) cyclotriphosphazene flame retardant to polycarbonate. During the blending process, the quaternary ammonium salt cation on the surface of the modified glass fiber interacts electrostatically with the sulfonate anion of hexa(sulfonic acid carbazole aniline) cyclotriphosphazene, thereby modifying the hexa(sulfonic acid carbazole aniline) cyclotriphosphazene flame retardant to the surface of the glass fiber. The two form a flame-retardant glass fiber composite material. Hexa(sulfonic acid carbazole aniline) cyclotriphosphazene, as a sulfonate-based nitrogen-phosphorus flame retardant, contains a large amount of aromatic ring structure and has good carbonization property. At the same time, the sulfonate structure can catalyze the isomerization of polycarbonate during combustion, promote the carbonization of polycarbonate, thereby forming a continuous and dense carbon layer on the surface of the glass fiber. The two form a composite carbon-glass fiber barrier layer, which has the functions of heat insulation, oxygen isolation, and preventing molten droplets, and has a good synergistic flame retardant effect. The limiting oxygen index of polycarbonate is significantly improved, and the UL94 fire rating reaches V-0.

[0018] The surface of the modified glass fiber of the invention is modified with organic functional groups such as quaternary ammonium salt, hexa(sulfonic acid carbazole aniline)cyclotriphosphazene, etc., which improves the compatibility with polycarbonate, enables the glass fiber to be evenly dispersed in the polycarbonate matrix, and more effectively exerts its reinforcing effect, thereby improving the tensile strength and bending modulus of the polycarbonate. DETAILED DESCRIPTION

[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0020] The glass fiber of the present invention is short-cut glass fiber with a fiber length of 3-4.5 mm and an average fiber diameter of 13 μm.

[0021] Example 1

[0022] The chopped glass fiber is placed in a radio frequency plasma device for plasma pretreatment, with the power set to 800W, the frequency set to 25kHz, and the gas source being dry compressed air; then the glass fiber is placed in an ethanol aqueous solution containing dimethyloctadecyl[3(-trioxymethylsilyl)propyl]ammonium chloride and ethyl orthosilicate and immersed for 3 minutes, wherein the volume ratio of dimethyloctadecyl[3(-trioxymethylsilyl)propyl]ammonium chloride and ethyl orthosilicate is 1:3, and the volume fraction of the ethanol aqueous solution is 90%; finally, the glass fiber is placed in an oven for a chemical grafting reaction at 120°C for 2 hours, and after the reaction, it is washed with water and dried to obtain a quaternary ammonium salt modified glass fiber.

[0023] (2) 3 mmol hexachlorocyclotriphosphazene, 19.8 mmol 9-(4-aminophenyl)carbazole hydrochloride, and 36 mmol pyridine were added to 20 mL xylene solvent, stirred at 90° C. for 48 h in a nitrogen atmosphere, and the solvent was concentrated, washed with acetone, and dried to obtain hexa(carbazoleanilino)cyclotriphosphazene. The structural formula is as follows:

[0024]

[0025] (3) At -20°C, 3 mmol hexa(carbazole aniline) cyclotriphosphazene was added to 8 mL of dichloromethane, 54 mmol chlorosulfonic acid was added dropwise, mixed and reacted at 25°C for 12 h, the solvent was concentrated, washed with acetone, the product was added to a potassium hydroxide solution with a pH of 9, reacted for 3 h, filtered, washed with water, and dried to obtain hexa(sulfonic acid carbazole aniline) cyclotriphosphazene. The structural formula is as follows:

[0026]

[0027] (4) 20 g of quaternary ammonium salt modified glass fiber and 0.5 g of hexa(sulfonic acid carbazole aniline) cyclotriphosphazene were added to a twin-screw extruder, the screw speed was set to 20 r / min, the blending temperature was set to 80°C, and the mixture was mixed for 5 min; then 1 kg of polycarbonate was added, the blending temperature was set to 270°C, the mixture was blended for 5 min, and the mixture was extruded to obtain a glass fiber composite material flame retardant modified polycarbonate material.

[0028] Example 2

[0029] (1) 3 mmol hexachlorocyclotriphosphazene, 18 mmol 9-(4-aminophenyl)carbazole hydrochloride, and 39 mmol pyridine were added to 30 mL toluene solvent, stirred at 80° C. in a nitrogen atmosphere for 72 h, the solvent was concentrated, washed with acetone, and dried to obtain hexa(carbazoleanilino)cyclotriphosphazene.

[0030] (2) At -10°C, 3 mmol hexa(carbazole aniline) cyclotriphosphazene was added to 12 mL of dichloromethane, 54 mmol chlorosulfonic acid was added dropwise, the mixture was mixed and reacted at 20°C for 24 h, the solvent was concentrated, the mixture was washed with acetone, the product was added to a potassium hydroxide solution at pH 9, the reaction was continued for 3 h, the mixture was filtered, washed with water, and dried to obtain hexa(sulfonic acid carbazole aniline) cyclotriphosphazene.

[0031] (3) 100 g of quaternary ammonium salt modified glass fiber (prepared according to the process of Example 1) and 1.5 g of hexa(sulfonic acid carbazole aniline) cyclotriphosphazene were added to a twin-screw extruder, the screw speed was set to 40 r / min, the blending temperature was set to 90° C., and mixing was performed for 5 min; then 1 kg of polycarbonate was added, the blending temperature was set to 260° C., blending was performed for 10 min, and extrusion was performed to obtain a glass fiber composite material flame retardant modified polycarbonate material.

[0032] Example 3

[0033] (1) 3 mmol hexachlorocyclotriphosphazene, 18.9 mmol 9-(4-aminophenyl)carbazole hydrochloride, and 39 mmol pyridine were added to 25 mL 1,4-dioxane solvent, stirred at 75° C. in a nitrogen atmosphere for 72 h, the solvent was concentrated, washed with acetone, and dried to obtain hexa(carbazoleanilino)cyclotriphosphazene.

[0034] (2) At -10°C, 3 mmol hexa(carbazole aniline) cyclotriphosphazene was added to 12 mL of dichloromethane, 72 mmol chlorosulfonic acid was added dropwise, the mixture was mixed and reacted at 15°C for 24 h, the solvent was concentrated, the mixture was washed with acetone, the product was added to a potassium hydroxide solution at pH 11, the reaction was continued for 2 h, the mixture was filtered, washed with water, and dried to obtain hexa(sulfonic acid carbazole aniline) cyclotriphosphazene.

[0035] (3) 200 g of quaternary ammonium salt modified glass fiber (prepared according to the process of Example 1) and 3 g of hexa(sulfonic acid carbazole aniline) cyclotriphosphazene were added to a twin-screw extruder, the screw speed was set to 40 r / min, the blending temperature was set to 70°C, and mixing was performed for 10 min; then 1 kg of polycarbonate was added, the blending temperature was set to 275°C, blending was performed for 5 min, and extrusion was performed to obtain a glass fiber composite material flame retardant modified polycarbonate material.

[0036] Comparative Example 1 is pure polycarbonate without adding quaternary ammonium salt-modified glass fiber (and hexa(sulfonic acid carbazole aniline)cyclotriphosphazene).

[0037] Comparative Example 2

[0038] 20 g of quaternary ammonium salt modified glass fiber and 1 kg of polycarbonate were added to a twin-screw extruder, the screw speed was set to 20 r / min, the blending temperature was set to 270° C., blended for 5 minutes, and extruded to obtain a modified polycarbonate material.

[0039] Comparative Example 3

[0040] 0.5 g of hexa(sulfonic acid carbazole aniline)cyclotriphosphazene and 1 kg of polycarbonate were added to a twin-screw extruder, the screw speed was set to 20 r / min, the blending temperature was set to 270° C., blended for 5 minutes, and extruded to obtain a modified polycarbonate material.

[0041] Comparative Example 4

[0042] 20g of glass fiber and 0.5g of hexa(sulfonic acid carbazole aniline)cyclotriphosphazene were added to a twin-screw extruder, the screw speed was set to 20r / min, the blending temperature was set to 80°C, and mixing was performed for 5min; then 1kg of polycarbonate was added, the blending temperature was set to 270°C, blending was performed for 5min, and extrusion was performed to obtain a glass fiber composite material flame retardant modified polycarbonate material.

[0043] The polycarbonate material was placed in an injection molding machine at an injection molding temperature of 260°C and injection molded into a standard specimen for performance testing.

[0044] Table 1 Performance test of polycarbonate materials

[0045]

[0046] As shown in Table 1, Comparative Example 1 is pure polycarbonate, the limiting oxygen index is only 21.8%, the UL94 fire rating is V-2, the flame retardancy is poor, and the tensile strength and flexural modulus are low.

[0047] Quaternary ammonium salt modified glass fiber and six (sulfonic acid carbazole aniline) cyclotriphosphazene flame retardant are added in embodiment 1 to 3. In the blending process, the quaternary ammonium salt cation on the surface of the modified glass fiber interacts electrostatically with the sulfonate anion of six (sulfonic acid carbazole aniline) cyclotriphosphazene, thereby the six (sulfonic acid carbazole aniline) cyclotriphosphazene flame retardant is modified to the glass fiber surface. Both form a glass fiber composite material with flame retardancy, significantly improve the limiting oxygen index of polycarbonate, and the UL94 fire rating reaches the V-0 grade. The modified glass fiber surface is modified with organic functional groups simultaneously, improves the compatibility with the polycarbonate, makes the glass fiber evenly dispersed in the polycarbonate matrix, more effectively brings into play its reinforcement, significantly improves the tensile strength and the flexural modulus of polycarbonate.

[0048] Compared with Example 1, Comparative Example 2 only added quaternary ammonium salt modified glass fiber, and the tensile strength and flexural modulus of polycarbonate were significantly improved. However, the flame retardant performance was poor.

[0049] In Comparative Example 3, only hexa(sulfonic acid carbazole aniline)cyclotriphosphazene flame retardant was added, which improved the flame retardancy of polycarbonate, but the tensile strength and flexural modulus were poor.

[0050] Compared with Example 1, in Comparative Example 4, unmodified glass fiber and hexa(sulfonic acid carbazole aniline)cyclotriphosphazene are added, and the glass fiber surface is not modified with organic functional groups, and the compatibility between the glass fiber and the polycarbonate is not improved, and the reinforcing effect is not better exerted, and the tensile strength and flexural modulus of the polycarbonate are not improved. In addition, the glass fiber surface does not contain quaternary ammonium salt cations, and electrostatic interaction cannot occur with the sulfonate anions of hexa(sulfonic acid carbazole aniline)cyclotriphosphazene, and hexa(sulfonic acid carbazole aniline)cyclotriphosphazene cannot be modified to the glass fiber surface, and the two do not form a good synergistic flame retardant effect, resulting in a limiting oxygen index lower than that of Example 1.

[0051] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A preparation process of a flame-retardant modified polycarbonate material of a glass fiber composite material, wherein the polycarbonate material comprises 100 parts by weight of polycarbonate, 0.05-0.3 parts by weight of hexa(sulfonic acid carbazole aniline)cyclotriphosphazene, and 2-20 parts by weight of quaternary ammonium salt modified glass fiber; The preparation process comprises: adding quaternary ammonium salt modified glass fiber and hexa(sulfonic acid carbazole aniline) cyclotriphosphazene into a twin-screw extruder, setting the screw speed to 20-40 r / min, the blending temperature to 70-90° C., and mixing for 5-10 minutes; then adding polycarbonate, setting the blending temperature to 260-275° C., blending for 5-10 minutes, and extruding to obtain a glass fiber composite material flame retardant modified polycarbonate material; The preparation process of the hexa(sulfonic acid carbazole aniline)cyclotriphosphazene is as follows: (1) adding hexachlorocyclotriphosphazene, 9-(4-aminophenyl)carbazole hydrochloride and pyridine to a reaction solvent, stirring and reacting in a nitrogen atmosphere, concentrating the solvent, washing with acetone and drying to obtain hexa(carbazoleanilino)cyclotriphosphazene; (2) adding hexa(carbazole aniline) cyclotriphosphazene to dichloromethane at -20°C to -10°C, adding chlorosulfonic acid dropwise, mixing well, reacting at 15-25°C for 12-24h, concentrating the solvent, washing with acetone, adding the product to potassium hydroxide solution, reacting for 2-3h, filtering, washing with water, and drying to obtain hexa(sulfonic acid carbazole aniline) cyclotriphosphazene; The molar ratio of hexachlorocyclotriphosphazene, 9-(4-aminophenyl)carbazole hydrochloride and pyridine in (1) is 1:(6-6.6):(12-13); In said (1), the reaction temperature is 75-90°C and the reaction time is 48-72h; The molar ratio of hexa(carbazoleanilino)cyclotriphosphazene to chlorosulfonic acid in (2) is 1:(18-24); The preparation process of the quaternary ammonium salt modified glass fiber is as follows: short chopped glass fibers are placed in a radio frequency plasma device for plasma pretreatment; the glass fibers are then immersed in an ethanol aqueous solution containing dimethyloctadecyl[3(-trioxymethylsilyl)propyl]ammonium chloride and ethyl orthosilicate; and finally the glass fibers are placed in an oven for chemical grafting reaction to obtain the quaternary ammonium salt modified glass fibers.

2. The preparation process of the flame-retardant modified polycarbonate material made of glass fiber composite material according to claim 1, characterized in that: The solvent in (1) is any one of toluene, xylene and 1,4-dioxane.

3. The preparation process of the flame-retardant modified polycarbonate material of glass fiber composite material according to claim 1, characterized in that: The pH of the potassium hydroxide solution in (2) is 9-11.

Citation Information

Patent Citations

  • Glass fiber reinforced polycarbonate molding compound with improved toughness

    CN107690453B

  • Carbazolylpolyphosphazene-containing electrochromic material, and preparation method and application thereof

    CN105237774A

  • Carbazole compound, carbazolyl group-containing polyester, composition for coating film, organoelectroluminescent element and display medium

    JP2010083770A